2D Animation: The Key to Growth and Adaptation of the South African Animation Ecosystem - Gardiner, Eric (University of the Witwatersrand, Johannesburg, 2024)
This paper examines South African animation with a focus on unveiling how local animators have adapted to overcome the challenges existing in their local circumstances. This research investigates the history of different techniques used by animators in South Africa and how they have evolved or died out. The data from a collection of over 170 locally produced animations is combined with opinion data from industry professionals to paint a clearer picture of current attitudes, trends and future trajectories. The cultural significance of localised animation is emphasised, and the core rhetoric of this paper is to stimulate the creation of more such media. This paper provides the most value to startup animators in South Africa who can leverage this collection of resources and information to bridge their gap in knowledge on South African industry processes such as financing one’s first animation project and developing a low-cost pipeline. The research in this paper uncovered that 2D animation plays the most significant role out of all techniques used in South Africa. It also reveals three differing business strategies that have been employed by South African animators to successfully fund locally themed animation productions.
A research report Submitted in fulfillment of the requirements of the degree of Master of Digital Arts in the field of Digital Animation by Research and Creative work, In the Faculty of Humanities , School of Arts, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; AnimationA; frica; AfrimationD; igital; Culture; HistoryP; itch Bible; African Stories Animation Technology; Animation Theory; SDG-9: Industry, innovation and infrastructure